2017
DOI: 10.1007/s00122-017-2972-7
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating wheat breeding for end-use quality with multi-trait genomic predictions incorporating near infrared and nuclear magnetic resonance-derived phenotypes

Abstract: Using NIR and NMR predictions of quality traits overcomes a major barrier for the application of genomic selection to accelerate improvement in grain end-use quality traits of wheat. Grain end-use quality traits are among the most important in wheat breeding. These traits are difficult to breed for, as their assays require flour quantities only obtainable late in the breeding cycle, and are expensive. These traits are therefore an ideal target for genomic selection. However, large reference populations are req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 36 publications
11
116
0
Order By: Relevance
“…Model predictive ability using single-trait prediction through CV1 with 40% of randomly masked individuals (198 individuals) was lower (between 0.24 and 0.43) than previously found in Battenfield et al 2016 (between 0.45 and 0.60) predicted using 20% randomly masked individuals. In addition, they were higher than those found in Hayes et al (2017) although the strategy used to predict performance was different; here, we used cross-validation approaches and Hayes et al (2017) predicted traits across years and locations.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Model predictive ability using single-trait prediction through CV1 with 40% of randomly masked individuals (198 individuals) was lower (between 0.24 and 0.43) than previously found in Battenfield et al 2016 (between 0.45 and 0.60) predicted using 20% randomly masked individuals. In addition, they were higher than those found in Hayes et al (2017) although the strategy used to predict performance was different; here, we used cross-validation approaches and Hayes et al (2017) predicted traits across years and locations.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, simulated and empirical studies show that multi-trait models were useful for predicting traits when individuals were partially phenotyped (Rutkoski et al 2012; Jia and Jannink 2012; Guo et al 2014; Rutkoski et al 2016; Hayes et al 2017; Sun et al 2017). Both Rutkoski et al 2012 and Sun et al (2017) found advantages of multi-trait models using correlated traits from high-throughput phenotyping (i.e., NDVI and canopy temperature) in wheat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GS has indeed shifted the paradigm in plant and animal breeding and has the potential to deliver more accurate predictions, reduce cycle time, reduce the cost of phenotyping, and facilitate rapid gains from selection (Muir 2007; Heffner et al 2009; van der Werf 2009; Jannink et al 2010; Hayes et al 2013). While several studies demonstrate the usefulness of GS for complex traits in wheat (Crossa et al 2014; Battenfield et al 2016; Hayes et al 2017; Juliana et al 2017a, b; Pérez-Rodríguez et al 2017), one of our key objectives was to evaluate both forward and backward genomic predictions for GY across different nurseries and years, and also explore the potential of utilizing GS in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…al. [14] introduced a reaction norm model 28 which introduces the main and interaction effects of markers and environmental covariates by using 29 high-dimensional random variance-covariance structures of markers and environmental covariates. 30 While most of the genomic prediction studies have been on individual traits, breeding programs use 31 selection indices based on several traits to make breeding decisions.…”
mentioning
confidence: 99%